PERBANDINGAN HASIL SIMULASI SOFTWARE PRIMO DENGAN PENGUKURAN EKSPERIMEN PADA QUALITY ASSURANCE BERKAS FOTON LINEAR ACCELERATOR VARIAN CLINAC CX - Wulandari Roelyant; Rico Adrial; Muhammad Arif Efendi (Universitas Andalas, 2026)
This study aims to compare the results of Monte Carlo simulations using PRIMO software with the results of experimental measurements in the QA process of a 6 MV Varian Clinac CX Linear Accelerator (LINAC) photon beam based on the parameters of Percentage Depth Dose (PDD), dose profile, and gamma index. Dose distribution measurements were performed using a water phantom at a Source to Surface Distance (SSD) of 100 cm with field sizes of 4×4 cm², 10×10 cm², and 40×40 cm². Monte Carlo simulations were performed using PRIMO software by modeling the geometry of the Varian Clinac CX LINAC head and water phantom according to the experimental conditions. The simulation and measurement results were analyzed through PDD curves, dose profiles, and quantitative evaluation using the gamma index with a tolerance criterion of 2%/2 mm. The results showed that the simulated PDD curves were in good agreement with the measurement results. The gamma passing rate values obtained were 97.98% for the 4×4 cm² field, 97.43% for the 10×10 cm² field, and 87% for the 40×40 cm² field. The decrease in conformity in large fields is influenced by an increase in the contribution of lateral scattering. The dose profile analysis results show conformity in the central area of the field, while greater differences occur in the penumbra and shallow depths due to steep dose gradients and detector resolution limitations. PRIMO-based Monte Carlo simulation can be relied upon as an independent verification instrument in the routine quality assurance of 6 MV photon beams from the Varian Clinac CX LINAC